Advantage of meditation over exercise in reducing cold and flu illness is related to improved function and quality of life. Issue 6 (21st November 2012) - Obasi, Chidi N.; Brown, Roger; Ewers, Tola; Barlow, Shari; Gassman, Michele; Zgierska, Aleksandra; Coe, Christopher L.; Barrett, Bruce
<x xml:space="preserve">Abstract</x> Please cite this paper as: Obasi et al. (2012) Advantage of meditation over exercise in reducing cold and flu illness is related to improved function and quality of life. Influenza and Other Respiratory Viruses 00(0), 00–00. Purpose To examine whether apparent advantages following training in meditation over exercise can be attributed to specific symptoms, functional impairments, or quality‐of‐life indicators assessed by the Wisconsin Upper Respiratory Symptom Survey (WURSS‐24). Methods Results from the randomized controlled trial "Meditation or Exercise for Preventing Acute Respiratory Illness" showed mean global severity and total days of illness were worse in control (358, 8·9) compared with exercise (248, 5·1) or meditation (144, 5·0). Global severity of illness was estimated using area under the curve from daily self‐reported severity scores on the WURSS‐24. For this project, we estimated within‐group WURSS item‐level severity and between‐group effect sizes (Cohen's "d" statistic) relative to control. The item‐level effect sizes were grouped into (i) symptom and (ii) function and quality of life domains. Results Among the three groups, mediators showed the lowest severity estimates for 21 of 22 WURSS items. Item‐level Cohen's "d" indicated most benefit was evident in WURSS items representing function and quality of life. Compared with exercise, meditation fostered larger reductions in illness severity, although due mostly to improved function and the quality of life domain (d = −0·33, P < 0·001) compared with symptom domain (d = −0·22, P < 0·001). Conclusions The apparent advantage of training in meditation over exercise for reducing cold and flu illness is explained more by improved function and quality of life than by a reduction in symptom severity.